2011
DOI: 10.1088/0957-4484/22/31/315704
|View full text |Cite
|
Sign up to set email alerts
|

Wettability changes of TiO2nanotube surfaces

Abstract: This study examines the effect of environmental and experimental conditions, such as temperature and time, on the wettability properties of titania nanotube (TNT) surfaces fabricated by anodization. The fabricated TNTs are 60-130 nm inner diameter and 7-10 µm height. One-microliter water droplets were used to define the wettability of the TNT surfaces by measuring the contact angles. A digital image analysis algorithm was developed to obtain contact angles, contact radii and center heights of the droplets on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
99
3
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(118 citation statements)
references
References 29 publications
7
99
3
6
Order By: Relevance
“…Studies demonstrate that the nanoscale morphologies display different wettability behaviour as compared to their microscale counterparts. 40,41 In general, the physics of liquid droplet interactions with nanostructured 40 and microstructured 41 surfaces have been the subject of increasing interest in the past few years.…”
Section: Page 7 Of 29mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies demonstrate that the nanoscale morphologies display different wettability behaviour as compared to their microscale counterparts. 40,41 In general, the physics of liquid droplet interactions with nanostructured 40 and microstructured 41 surfaces have been the subject of increasing interest in the past few years.…”
Section: Page 7 Of 29mentioning
confidence: 99%
“…40,42,43 For example by the aid of plasma treatment technique, the hydrophobic character of aged TiO 2 nanopore/nanotube surface will be reversed to hydrophilic, possibly due to the removal of surface contaminants, such as carbon. It was shown recently that wettability of TiO 2 nanosurfaces can change with time.…”
Section: Fabrication Of Tio 2 Surfacesmentioning
confidence: 99%
“…44 After the anodization process, the droplet contact angles decreased in the range of 55%~70% compared to the bare substrate. This indicates that the creation of nanotube structures makes the surface more hydrophilic.…”
Section: Fe-sem Imagesmentioning
confidence: 99%
“…The rationale behind such a conclusion is that nanotube surfaces enhance surface energy as well as hydrophilicity of the surface due to the presence of functional hydroxyl groups on the surface. 44 Considering that proteins are better absorbed on the hydrophilic TiO 2 nanotube surfaces, cell adhesion is enhanced. This hypothesis is in agreement with Yao et al's study 46 which reported that the initial adsorption of proteins on anodized nanotube Ti was increased compared to anodized nanoparticles and un-anodized Ti.…”
mentioning
confidence: 99%
“…[18][19][20][21] TNTs also improve the physiochemical characteristics of surfaces as shown through their ability to maintain surface wettability for a period of at least one month compared to smooth or rough Ti surfaces. [22][23][24] Hydrophilic surfaces attract more bronectin (FN) and vitronectin (VN) protein from the body uids, which are essential sites for cellular attachment and proliferation.…”
Section: 11mentioning
confidence: 99%